2010
DOI: 10.1002/app.31679
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and thermal stability of cellulose‐graft‐polyacryloniytrile prepared by using KMnO4/citric acid redox system

Abstract: An effective condition of graft polymerization of acrylonitrile onto cellulose fiber in large volume of KMnO 4 /citric acid aqueous solution was examined and the produced grafted copolymers were characterized by using SEM, NMR, FTIR, XRD, TGA, and DSC in comparison with component homopolymers. Graft yield, GY, obtained by simple weighting method was close to the value obtained by NMR analysis. Significant change of chemical structure in cellulose fiber, other than graft reaction, was not detected by NMR and FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 32 publications
(26 reference statements)
3
20
0
1
Order By: Relevance
“…Figure 4 shows the 13 C CP-MAS spectra of Un-C and C-g-PAN samples prepared by using different acids in the graft copolymerization. As reported in the previous study 29) , the resonances belonging to the cellulose (60-110 ppm) are well observed in the all spectra. Also the resonance peaks related to the grafted chain (40 ppm) are observed in the all spectra of C-g-PAN samples.…”
Section: Characterizationsupporting
confidence: 87%
See 4 more Smart Citations
“…Figure 4 shows the 13 C CP-MAS spectra of Un-C and C-g-PAN samples prepared by using different acids in the graft copolymerization. As reported in the previous study 29) , the resonances belonging to the cellulose (60-110 ppm) are well observed in the all spectra. Also the resonance peaks related to the grafted chain (40 ppm) are observed in the all spectra of C-g-PAN samples.…”
Section: Characterizationsupporting
confidence: 87%
“…As reported previously 29) , the grafted-PAN only partially covered the cellulose surface so that the morphological characteristics of cellulose microfibrils are still visible in the grafted samples.…”
Section: Characterizationsupporting
confidence: 75%
See 3 more Smart Citations